Availability and accessibility of cytotoxic medicines in the WHO model list of essential medicines for childhood cancer in low and lower-middle- income countries: a systematic review - Maheeka Seneviwickrama; Sashini Shehana Denagamagei; Surangi Jayakody; Sanjeeva Gunasekera; Guwani Liyanage (BMC Cancer)
Abstract Background Socio-economic inequalities significantly impact paediatric cancer survival. The review aims to elucidate the facilitators and barriers influencing the availability and accessibility of essential medicines for childhood cancer (EMCC) in low- and lower-middle-income countries (LLMICs). Methods This systematic review was conducted adhering to the PRISMA guidelines. Peer- reviewed primary studies, national/regional reports, and policy documents published in the English language were included through a thorough literature search using three electronic databases: MEDLINE, EMBASE, and CINAHL. Review questions were framed according to the ECLIPS framework. Children under 19 years of age living in LLMICs diagnosed with any malignancy were the client group. The quality of the included studies was assessed using the mixed methods appraisal tool. Data is presented as a narrative synthesis. Enablers and barriers were discussed based on the World Health Organization (WHO) health system building blocks. Results Out of the 29 articles retrieved for full-text screening, the final synthesis included nine articles. Six were based on quantitative, two on mixed-method research, and one was a review article. These studies represented 26 LLMICs from several continents (Africa, Asia, and America). The alignment of the National Essential Medicine Lists (NEMLs) with the World Health Organization Essential Medicine List for Children (WHO EMC) varied from 40%- 60%. Overall stock out rate ranged from 17 to 100%. Stock out rate was higher in the public sector than in the private sector. International partnerships, policy changes, and financing strategies are some of the key enablers identified. Barriers included inadequate global drug production, high drug costs, weak regulatory enforcement, poor supply chain management, and insufficient health information systems. Conclusion The findings of our review revealed the failure of LLMICs to meet the WHO- recommended target of 80% availability for EMCCs. The availability and accessibility of EMCC in LLMICs are hindered by multiple systemic barriers despite several enabling strategies. Addressing these challenges requires coordinated global efforts and local initiatives to ensure equitable access to childhood cancer treatments in LLMICs. PROSPERO registration number CRD42022334156.